EXPERIMENTAL STUDY OF FE-MG EXCHANGE REACTION BETWEEN ORTHOPYROXENE AND SAPPHIRINE AND ITS CALIBRATION AS A GEOTHERMOMETER - Kawasaki T.; Sato K. (My University, 2002)
The exchange of Fe2+ and Mg2+ between orthopyroxene and sapphirine has been investigated at pressures 7-16 kbar and temperatures 850-1300°C using a piston cylinder apparatus for the synthetic and natural systems. This reaction is temperature-dependent and would be a good geothermometer. The equilibration temperature T is approximately expressed by the distribution coefficient as follows: T(°C)=1515/(ln KD+0.943)-273.This empirical equation was applied to some Antarctic granulites and associated rocks. The new orthopyroxene-sapphirine geothermometer gives consistent results with those estimated from the Fe-Mg orthopyroxene-garnet geothermometer.